Implementation of a manual stacker to reduce the labor absenteeism at the enterprise Rioimpresiones - Negrete Costales, José Hernán; López Naranjo, Alexandra Lorena (mktDESCUBRE; Vol 1 No 13 (2019): Thirteenth Edition - (January - June), 2019)
The present study was developed at the enterprise Rioimpresiones of the city of Riobamba, Chimborazo province , Ecuador. The type of research was documentary, field and descriptive; the methodology used had a quantitative approach; The technique used dealt with  interviews and for the data collection a questionnaire was established as an instrument. The research hypothesis consisted of demonstrating that the implementation of a manual stacker can reduce absenteeism at the enterprise Rioimpresiones. In the first investigation stage, a historical study, related to labor absenteeism was conducted. In the second stage, it was determined how labor absenteeism negatively affects the operating costs of the company. In the third stage, the use of a manual stacker was implemented to transport loads and thus determine the decrease of labor absenteeism problems. In the fourth and last stage, the hypothesis testing was carried out for which the enterprise was evaluated to determine if the use of the manual stacker decreases the company's absenteeism from work. As a result of the investigation, it was possible to demonstrate that the use of an industrial safety tool, reduced the absenteeism of work and, consequently, reduced the operative costs of the enterprise.